GAYO LANGUAGE IS OLD MALAY (A DIALECTOLOGY STUDY: THE LANGUAGE CHANGE) - Abdussalam Abdussalam; Salami Mahmud (Englisia: Journal of Language, Education, and Humanities, 2014)
An interdisciplinary linguistic which studies the problem on language variation is so called Dialectology. The variation of language happens on the usage that is caused by the change of social environment and place for ages. Language variation can be found in the form of accent, sub dialect, dialect, or that of language. Studying a language variation means also to trace the language history. Geographically, language variation can show where the speaker comes from. Linguistics distinctions analyzed in dialectology are phonetics, morphemic, and lexical variations. However, in this study, phonological and lexical variations are discussed. Glosses used are Ogden's 850 basic words which have been translated into Bahasa. The research subjects are 18 Gayo native speakers. Six of them become primary informants and the rests are as secondary ones. Methods of acquiring data used are cakap-simak (speak and listen) as well as tulis-rekam (write and record). The discovered data from the informants are crosschecked with the standardized words of Kamus Besar Bahasa Indonesia (Indonesian Great Dictionary). Then, the distance of word variations are determined by using dialectometry formula. The result are: 165 words = 19,41% lexical differences, 305 words = 35,88% phonetically differences, and 380 words = 44,71% without difference, neutral or zero. By regarding 1% data error tolerant, it can be concluded that Gayo language is Old Malay that has “accent variation = 20,41%" compared to New Malay or Bahasa Indonesia.